Tilepadeion : I know what's in your mind - Casal, Joaquim (Narrativa Milenio., 2018)
The paths of the intellectually restless scientist Adam Barnes and the equally restless international spy Shedarak cross in a journey that takes them from San Francisco to Akademgorodok, Edinburgh to Barcelona, in an unrelenting game of cat and mouse to find out what is being concealed, and to conceal what is known.